Media Relations Activities as A Public Relation Strategy Implementation of PT. Toyota Astra Motor - Prabowo, Galih Akbar (UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Abstract: Public relations have an important role in a company. Not only in the effort to ensure good relations with the internal stakeholders, but also with its external stakeholders. In relation to external stakeholders, the media is one of the parties that have important roles in the formation of the company image. PT. Toyota Astra Motor as an international scale automotive company is an example of a company that owns a large commitment to building a good relation with media. Media relations activities conducted by the company have been proving that PT. Toyota Astra Motor not only placed the press as an instrument to build a positive image of the company but even more than that, the media is one of the important stakeholders and a partner for the PT. Toyota Astra Motor Itself.